Ask a New Question
Search
Questions and answers by
mtd
Questions (2)
sorry, another I can't figure out
Show that (1-cot^2x)/(tan^2x-1)=cot^2x I started by factoring both as difference of squares.
2 answers
670 views
square root(a^2 -u^2) where a>0, let u=(a sinx) where -pi/2<x<pi/2
answer is (a cosx) and I don't know how to get there
1 answer
382 views
Answers (3)
I believe the noble gas group or Group O. Hopefully someone can verify that. I apologize if that is wrong.
Take the two equation two unknown down to one unknown by either adding or subtracting the second equation from the first so that one of the uknowns is removed. 2x+y=5 + x-y=1 -------------- 3x=6 x=2 Then plug the newly found x value into one of the
let me try to type it out again, my apologies. Original problem is--Prove the following: 1- cot^2 x ----------- = cot^2 x tan^2 x - 1 That is how the problem actually looks.